Моделі штучного інтелекту для управління та оптимізації peer-to-peer мереж - Кучук, А. О. (ХНУРЕ, 2023)
The use of artificial intelligence methods in peer-to-peer networks is a very relevant topic, as the growth of Internet traffic leads to an increase in the amount of data that must be processed and transmitted over the network. AI methods can improve data exchange processes in such networks, increase their speed and efficiency, and provide greater security and protection against attacks.